Microribbons composed of directionally self-assembled nanoflakes as highly stretchable ionic neural electrodes - Zhang, Mingchao; Guo, Rui; Chen, Ke; Wang, Yiliang; Niu, Jiali; Guo, Yubing; Zhang, Yong; Yin, Zhe; Xia, Kailun; Zhou, Binghan; Wang, Huimin; He, Wenya; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Many natural materials possess built-in structural variation, endowing them with superior performance. However, it is challenging to realize programmable structural variation in self-assembled synthetic materials since self-assembly processes usually generate uniform and ordered structures. Here, we report the formation of asymmetric microribbons composed of directionally self-assembled two-dimensional nanoflakes in a polymeric matrix during three-dimensional direct-ink printing. The printed ribbons with embedded structural variations show site-specific variance in their mechanical properties. Remarkably, the ribbons can spontaneously transform into ultrastretchable springs with controllable helical architecture upon stimulation. Such springs also exhibit superior nanoscale transport behavior as nanofluidic ionic conductors under even ultralarge tensile strains (> 1,000%). Furthermore, to show possible real-world uses of such materials, we demonstrate in vivo neural recording and stimulation using such springs in a bullfrog animal model. Thus, such springs can be used as neural electrodes compatible with soft and dynamic biological tissues.